The impact of internet games on the Performance of Criminology student of the University of Mindanao Bansalan College - Domingo, Anthony; Gometer, Ephraim; Luayan, Clark (--Davao del Sur: UM Bansalan College., 2017)
This study was conducted to determine the Impact Of Internet Games on the Performance of the Criminology Student of the University of Mindanao Bansalan College. The researchers aimed to to determined the significant difference in the impact of internet games on the performance of criminology students when analyzed by profile. The study was conducted using the descriptive correlation method. The researchers administrated personally the questionnaire to the chosen respondents of the University of Mindanao Bansalan College with 100 participants. The study resulted to data and findings which determine the impact of internet gameson the performance of criminology students was strongly agreed, which denotes high impact. The significant difference on the Impact of Internet Games on the Performance of the Criminology Student's of the University of Mindanao College got the computed P-values is 0.42 and 0.009 and was tested below 0.05 level of significant. Based on the findings and conclusions the researchers would like to recommend that the internet use for academic assignment and research must be allocated so that the student can spend time for studying and reading books and in as much as the level of impact of internet games on the performance of criminology students, is in concerned the student's must put limit to their internet usage, so that the eating habit and lying to the family can be lessen and their health can save from any sickness, further, the parents and guardian must always pay attention about the internet usage of their student and always in attention on the actions and doings of their student, and the students also must pay attention for their health and their safety in order to have better future.